Structure and Properties of α-Fe2O3 Based on Natural Iron Sand through Low-Temperature Process as an Adsorbent of Metal Ion Mn - Indrawati, Wiwik; Simbolon, Silviana; Apadi, Mochammad Rizky; Prijono, Kusdi; Nugroho, Edo Prasetyo; Yunus, Muhammad (EduChemia: Jurnal Kimia dan Pendidikan, 2025)
One of the countermeasures against heavy metal environmental pollution is through an adsorption process utilizing nanoparticle technology, one of which uses hematite (α-Fe2O3) nanoparticles. In this study, the manufacture of α-Fe2O3 nanoparticles derived from natural iron sand through the process of precipitation as adsorbent of the heavy metal manganese (Mn) was carried out. The variable used is the temperature of the coprecipitation process in the range of 60–80°C. Furthermore, characterization and adsorptivity tests of α-Fe2O3 nanoparticles against the heavy metal ion Mn were carried out. The synthesized α-Fe2O3 was characterized in terms of phase using XRD, morphological structure using SEM‒EDS, density using pycnometer and adsorption using AAS. The results obtained from XRD show that α-Fe2O3 crystallizes well in the (104) plane at the 2θ region of 35.612° and has the smallest crystal diameter of 3.03760 nm at 60°C. SEM revealed that there was still agglomeration in the results and a particle size distribution of 62 nm at 60°C. The density results revealed the highest value at 80°C, with a value of 30 g/cm3. However, the manganese (Mn) adsorption results revealed the optimal conditions for the value of the Mn content adsorbed at 70°C, namely, 2176 µ/g.